Productive Waqf Development Strategy to Advance Education and Health in the Bangka Belitung Islands Province - Efendi Sugianto (Pt. Anagata Sembagi Education, 2025)
Waqf is one of the important instruments in Islamic economics that has a strategic role in the social development of society, especially in the fields of education and health, in the Bangka Belitung Islands Province, the potential for waqf is quite large with more than 1,377 plots of waqf land spread across various regions but its management is still dominated by a consumptive approach and has not been developed productively, this article aims to examine the strategy of developing productive waqf as an alternative solution for financing education and health development, especially in areas that still have limited access to basic services. This study uses a descriptive qualitative approach with data collection methods through in-depth interviews, observation, and documentation. Research informants consist of waqf nazhir, community leaders, academics and related parties from the Ministry of Religious Affairs as well as waqf-based educational and health institutions. Data analysis was carried out with a thematic approach through the stages of data reduction, data presentation, and drawing conclusions. The research results show that low public literacy, unequal training for nazhir, and incomplete legality of waqf assets are the main obstacles in the development of productive waqf. However, there are initiatives that can serve as pilot models, such as the productive waqf incubation program by the KUA in East Belitung and South Belitung, and the management of oil palm agricultural waqf in Bedengung Village. The research also found that multi-stakeholder collaboration, management transparency, and digital technology support play a significant role in encouraging sustainable productive waqf. Thus, the strategy for developing productive waqf in Bangka Belitung requires synergy between the government, nazhir, the community, and the private sector through asset legalization, increasing public literacy, nazhir training, and the integration of waqf into regional economic programs. Productive waqf is expected to be an alternative development instrument that can strengthen education and health services evenly and inclusively, and improve community welfare in a sustainable manner in the Bangka Belitung archipelago.